Analisis Isi Kekerasan Seksual di lembaga Pendidikan Pada Laman Kompas Online - Savvana, Alfinda Diana; Rostikawati, Rin; Martono , Nanang (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to describe the characteristics and forms of sexual violence in educational institutions reported on the Kompas Online page for the 2018-2022 period. This research uses descriptive quantitative content analysis method. The object studied was news of sexual violence in educational institutions for the period 2018-2022. Samples were taken using total sampling totaling 100 news cases. The results showed that all perpetrators of sexual violence in educational institutions reported were male (100%), and most victims of sexual violence were female (81%). Furthermore, the perpetrators of sexual violence are mostly dominated by teachers (43%). This is related to the unequal power relations between perpetrators and victims. Then, most sexual violence occurs in elementary schools (29%) due to several factors, such as victims tend to be innocent, have low knowledge about sex education, low levels of courage due to pressure or threats. Regarding the relationship between education level and forms of sexual violence, it shows that touching/poking, and touching in sensitive areas (breasts, genitals, etc.) occurred mostly in elementary schools (69.0%) and universities (45.5%). In addition, coercion of sexual intercourse outside of legal marriage occurred mostly at the high school (54.5%), junior high school (52.2%), and Islamic boarding school (46.7%) education levels. Then, in the category of the relationship between the perpetrator and the victim, which is dominated by teachers as perpetrators, it turns out that many commit sexual violence in the form of touching / poking and touching in sensitive areas (breasts, genitals, and others) (55.8%). This was done by the perpetrators to fulfill their sexual satisfaction by means of persuasion, the lure of gifts, and threats so that their victims, who were students, could be influenced and tricked.